Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒÙ„Ø§Ù… Ù…Ù†Ø¸ÙˆØ± Ù…Ù† Ø¹Ù…Ù„ÙŠØ© Ø§Ù„ØªØ¹Ù„Ù… ÙˆØ§Ù„ØªØ¹Ù„ÙŠÙ… ÙÙŠ Ø¬Ø§Ù…Ø¹Ø© Ø¨Ø§ØªÙˆØ³Ù†Ø¬ÙƒØ± Ø§Ù„Ø§Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„ØÙƒÙˆÙ…ÙŠØ© Ø³ÙˆÙ…Ø·Ø±Ù‰ Ø§Ù„ØºØ±Ø¨ÙŠØ© - Suharmon, Suharmon (Lughawiyah: Journal of Arabic Education and Linguistics, 2019)
This research aims to obtain infomation about Arabic learning especially speaking skill in Arabic Language Education Department at IAIN Batusangkar. The research uses a quantitative approach. The instruments to collect the data are test and questionnaire. The data were analyzed using descriptive statistics. The results of the research state that the studentsâ€™ speaking ability at class â€œ A â€œ are 28% low, 36% moderate, and 36% high. While, at class â€œBâ€, studentsâ€™ speaking abilities are 36.4% low, 40,9% moderate, and 22.7% high. The cause of studentsâ€™ low ability is the unappropriateness of teachersâ€™ strategy in teaching speaking. There are about 96% students at class â€œAâ€ agreed and 86.4% students at class â€œBâ€ had similar answer. Another cause is studentsâ€™ low motivation in learning. Class â€œAâ€ students agreed for about 76% of them and 77% of class â€œBâ€ students answered the same. From the finding, it can be concluded that the inability of students to speak Arabic can be overcomed by improving teaching strategies and encouraging maximum motivationÂ  to learn Arabic.